Fiscal Contingency Planning for Banking Crises - Honohan, Patrick 1949- (The World Bank, 1999)
November 1999 - Estimating the likely fiscal costs of future banking crises requires information about the size and composition of the banks' balance sheets and expert assessments about the accuracy of the accounting data and about certain short-term risks. There is constant demand for an estimate of the likely fiscal costs of future banking crises, but little precision can be expected in such an estimate. Honohan shows how information that is typically available to authorities could be used to get a general sense of the order of magnitude of the direct fiscal liability. What is required for such an estimate? · Information about the size and composition of the banks' balance sheets. · Expert assessments of the accuracy of the accounting data and of specific short-term risks to which the components are known to be subject. Honohan's method distinguishes between losses that have already crystallized and the changing risks for the immediate future. By including contingency planning for banking collapse in their fiscal calculations, authorities may risk destabilizing expectations or worsening the moral hazard in the system. But the risks of contingency planning generally outweigh the risks of sending confused signals. Insisting on ignorance is a poor way to protect against announcement errors that trigger panic. This paper - a product of Finance, Development Research Group - was produced for the Poverty Reduction and Economic Management Network thematic group studying the quality of fiscal adjustment. The author may be contacted at phonohan@worldbank.org